2005
DOI: 10.1016/j.jfluchem.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of insect sex pheromone analogs having a fluorine atom on their double bonds

Abstract: Insect sex pheromone analogs having a fluorine atom on their double bonds,were stereoselectively synthesized using cross-coupling reactions of alkenylboranes with (E)-or (Z)-2-fluoro-1-iodo-1-alkenes, stereoselectively prepared from 1-alkynes by our currently developed methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…38 Such a dependence on the anion used has never been reported previously in the formation of heteroaromatics from alkynyliodonium salts, though the literature suggests that the conversion of alkynyliodonium salts to alkenyliodonium salts appears to demonstrate stereoselectivity for the E-or Z-isomer depending on the counter-ion used. [45][46][47][48][49][50][51][52][53][54][55] The influence of solvent on ion pair separation, and hence choice of counterion, has also been shown to affect the reactions of diaryliodonium salts. 56 In addition to the counter-ion dependence of the reaction it was found that the concentration of the reactants also exerted an unexpected degree of control over the product distribution ( Table 2 and Fig.…”
Section: Introductionmentioning
confidence: 99%
“…38 Such a dependence on the anion used has never been reported previously in the formation of heteroaromatics from alkynyliodonium salts, though the literature suggests that the conversion of alkynyliodonium salts to alkenyliodonium salts appears to demonstrate stereoselectivity for the E-or Z-isomer depending on the counter-ion used. [45][46][47][48][49][50][51][52][53][54][55] The influence of solvent on ion pair separation, and hence choice of counterion, has also been shown to affect the reactions of diaryliodonium salts. 56 In addition to the counter-ion dependence of the reaction it was found that the concentration of the reactants also exerted an unexpected degree of control over the product distribution ( Table 2 and Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Guan, Hara, and their coworkers reported a convergent and stereoselective synthesis of fluorinated analogs of insect sex pheromones using (E)-and (Z)-2-fluoro-alkenyliodonium salts as the intermediates (Fig. 6) [26]. The simplicity, good reaction yields, and the high stereoselectivity of these synthetic pathways illustrated the advantages of this methodology in utilizing 2-fluoroalkenyliodonium salts to introduce a fluoroalkenyl moiety into the skeleton of organic molecules.…”
Section: Synthesis Of Multifunctionalized Fluoroalkenes Via Aryl-alkementioning
confidence: 99%
“…Thereby, (b-fluorovinyl)iodonium salts were converted to the iodofluoroalkenes 101, with 5 mol% of CuI and a stoichiometric amount of KI (Scheme 82), which are good coupling partners under Suzuki conditions (Table 21, entries 2-10). 188,207 Suzuki cross-coupling reactions with fluorovinyl-halide derivatives were applied for the stereoselective synthesis of fluorinated analogues of insect sex pheromones, 208 for the preparation of fluorinated analogues of resveratrol 209 and for the design of conformationally restricted peptidomimetics. 210 In 2006, Andrei and Wnuk reported a novel Negishi alkylation of 1-fluorovinyl-halide providing an interesting strategy for the use of sp 3 -carbone nucleophiles (i.e.…”
Section: Cross-coupling Reactionsmentioning
confidence: 99%